DO BRAND EXPERIENCE AND ELECTRONIC WORD OF MOUTH LEVERAGE THE SKINCARE BRAND TRUST? AN IVESTIGATION FROM INDONESIA - Nurul Aulia Ramadhina; Rajiv Dharma Mangruwa (SEAN Institute, 2023)
This skincare industry has massively changed into the new digital era. The study aims to investigate the impact of electronic word of mouth (E-WOM) and brand experience on brand trust for skincare business. The study used a quantitative descriptive research methodology through a survey. The 107-respondent obtained and analyzed using multiple linear regression analysis. The results proved that electronic word of mouth and brand experience provided by skincare products critically leverage building brand trust in cosmetic business. In other words, consumers a brand trust obtained significant leverage in current trends. The study recommends elaborating the observation of skincare business for future research.